Connecting Age-Related Biological Decline to Frailty and Late-Life Vulnerability - Walston, Jeremy D. (Nestle Nutr Inst Workshop Ser, 2015)
Frailty is an important construct in aging which allows for the identification of the most vulnerable subset of older adults. At least two conceptual models of frailty have been developed that have in turn facilitated the development of multiple frailty screening tools. This has enabled the study of populations of frail and nonfrail older adults, and facilitated the risk assessment for adverse health outcomes. In addition, using the syndromic approach to frailty, numerous biological hypotheses have been tested, which have identified chronic inflammatory pathway activation, hypothalamic-pituitary-adrenal axis activation, and sympathetic nervous system activity as important in the development of frailty. In addition, age-related molecular changes related to autophagy, mitochondrial decline, apoptosis, senescent cell development, and necroptosis likely contribute to the heterogeneous phenotype of frailty. The recent development of a frail mouse model with chronic inflammatory pathway activation has helped to facilitate further whole organism biological discoveries. The following article attempts to create an understanding of the connections between these age-related biological changes and frailty.